1996
DOI: 10.1017/s0017089500031372
|View full text |Cite
|
Sign up to set email alerts
|

On linear recurrence sequences with polynomial coefficients

Abstract: We consider sequences (Ah)defined over the field ℚ of rational numbers and satisfying a linear homogeneous recurrence relationwith polynomial coefficients sj;. We shall assume without loss of generality, as we may, that the sj, are defined over ℤ and the initial values A0A]…, An−1 are integer numbers. Also, without loss of generality we may assume that S0 and Sn have no non-negative integer zero. Indeed, any other case can be reduced to this one by making a shift h → h – l – 1 where l is an upper bound for zer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…We write the "little-c" recursion in this way for convenient connection with experimental results; for example, we have always encountered natural alternating signs, and some obvious factors of the polynomials p implicitly defined by (37). Note, for instance, that the experimental recursions (35) and (36) can be recast compactly in the form of (37) by defining Table 2 has many other p n,i polynomials that we have found experimentally.…”
Section: Recursion Relations-experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We write the "little-c" recursion in this way for convenient connection with experimental results; for example, we have always encountered natural alternating signs, and some obvious factors of the polynomials p implicitly defined by (37). Note, for instance, that the experimental recursions (35) and (36) can be recast compactly in the form of (37) by defining Table 2 has many other p n,i polynomials that we have found experimentally.…”
Section: Recursion Relations-experimentsmentioning
confidence: 99%
“…Most authors abide by the nomenclature as we do, namely, the order of the recursion is M , meaning there are M + 1 different C terms (and M + 1 polynomial coefficients). Some researchers refer to any sequence such as C, satisfying such a recursion, as holonomic, and observe that a generating function will satisfy a similar recurrence relation in its derivatives [37,47,20].…”
Section: Recursion Relations-experimentsmentioning
confidence: 99%
“…In fact, a slightly more precise version of Theorem 1.1 was proved by van der Poorten-Shparlinski [vdPS96,. Their method uses a technical construction of a certain auxiliary function.…”
Section: Introductionmentioning
confidence: 99%
“…Heights of coefficients of D-finite power series have been studied independently, notably by van der Poorten and Shparlinski [vdPS96], who showed a gap result holds in this context that is somewhat weaker than what is predicted by our height gap conjecture above; specifically, they showed that if n≥0 a(n…”
Section: Introductionmentioning
confidence: 90%